Issues and Future Perspective on Zinc Metal Anode for Rechargeable Aqueous Zinc‐ion Batteries. Issue 2 (12th February 2020) - Li, Canpeng; Xie, Xuesong; Liang, Shuquan; Zhou, Jiang
Abstract : Rechargeable aqueous zinc‐ion batteries (ZIBs) featuring the merits of low cost, eco‐friendliness, and enhanced safety have attracted extensive interests and considered as the most promising energy storage system. However, much efforts are devoted to the exploration of cathode materials and their storage mechanisms in this system, and inadequate attentions are received in regard to anode side especially in neutral or mild acidic electrolyte. Therefore, in this review, the fundamental understanding of existing issues including dendrite formation, corrosion, and hydrogen evolution are mainly revealed, as well as their interaction in neutral or mild acidic medium. In addition, the currently existing solution strategies on the anode are summarized and the mechanisms that contained are simultaneously investigated. Finally, perspectives on future anode modification and innovation direction are provided for the further development and research of Zn‐based ZIBs. Abstract : The recent advances and strategies summary of zinc metal anode in aqueous zinc‐ion batteries is timely provided. The fundamentals of issues facing zinc metal anode are discussed, as well as their interaction. Some perspective directions are proposed for the future development of zinc metal anode.